Dynamic stability of unguided projectile with 6- DOF trajectory modeling - Bashir, Musavir; Khan, Sher Afghan; Udayagiri, Leelanadh; Noor, Asim (IEEE Explorer, 2017)
The paper presents the study of unguided rolling projectiles at varying Mach numbers using aerodynamic coefficients. The aerodynamic coefficients are estimated using an aerodynamic prediction code, Missile DATCOM. The predicted dynamic derivatives will determine the design criteria, and also their effect on the design aspects (stability and accuracy) of the projectile. To satisfy the condition of stability for the trajectory of projectile, a model of 6 DOF equations has been used. The result parameters, such as static margin of the projectile, force and moment derivatives in all the three modes, spin rate, angle of attack, and time rate are shown. The accuracy of the rolling moment derivatives is uncertain due to the limitation of DATCOM, but it is the general method applicable at the initial design stage of any projectile and therefore falls in the realm of aerodynamic database. The results address the problems of static and dynamic stability by giving initial perturbations, effect of spin on thrust misalignment, and effect of variation in the geometric parameters during the power on and off cases. Therefore, there is a need for full aerodynamic characterization of the projectile, in which sufficient derivatives are computed for accurate results.